Anodic stripping voltammetry at flow-through electrodes: theory and experiment - Ball, J; Cooper, J; Compton, R (1997)
Numerical simulations based on the Time Dependent Backwards Implicit method are used to implement the theory of anodic stripping voltammetry peaks at mercury thin film channel electrodes. First the peakshape is found to be a sensitive function of both electrolyte flow rate and voltage sweep rate. Criteria are established to characterise the conditions under which symmetric or asymmetric peakshapes are expected. Second the mercury film is shown to be stripped in a spatially non-uniform fashion with the flow inducing the upstream part of the film to be depleted before, and at less positive potentials than that downstream. Implications for practical ASV are noted. Experiments on the ASV detection of Pb2+ at a well-characterised channel electrode are reported and the waveshapes measured as a function of solution flow rate are found to be in excellent agreement with theory. © 1997 Elsevier Science S.A.